Impact of Obturator Nerve Block on the Short-Term Recurrence of Superficial Bladder Tumors on the Lateral Wall - Tekgül, Zeki Tuncel; Divrik, Rauf Taner; Turan, Murat; Konyalioglu, Ersin; Simsek, Esen; Gönüllü, Mustafa (Urology Journal, 2014)
Purpose: The aim of this study was to compare the recurrence rates of patients with bladder tumors on the lateral wall undergoing transurethral resection of bladder tumor(TUR-BT) with or without obturator nerve block (ONB) and to investigate the impact of ONB on the effective tumor resection on the lateral bladder wall. Materials and Methods: All patients who underwent TUR-BT under spinal anesthesia within the three-year study period in the study center were reviewed retrospectively. Among these, 68 patients who had been diagnosed with de novo lateral bladder wall tumor and included in low risk group 1n accord with European Organization for Research and Treatment of Cancer (EORTC) classification, undergone complete resection were enrolled into the study. Group 1 (36 patients who underwent TUR-BT with only spinal anesthesia) and group 2 (32 patients who underwent TUR-BT with spinal anesthesia plus ONB) were evaluated with respect to tumor recurrence rates and disease-free time to recurrence, if any. Results: Follow-up periods (range, 19 to 41 months for group 1 and 19 to 39 months for group 2) and overall recurrence rates (group 1, 27.8% and group 2, 18.8%) were also found to be similar. Mean time to recurrence was significantly higher in group 2 (15 ± 5.5 months) than in group 1 (7.8 ± 4.5 months) (P = .009) Conclusion: ONB employed in addition to spinal anesthesia in TUR-BT involving the lateral wall can prolong time to recurrence and increase the chance to lengthen disease-free survival in low-risk superficial bladder tumors.